Geotechnical Characterization of Soils in the Eastern and Western Areas of Tehran - Razmyar, A.; Eslami, A. (Engineering, Technology & Applied Science Research, 2017)
Tehran is placed in a high seismic risk zone with specific natural hazards. The resources to deal effectively with a possible crisis are limited, so proper preparation is a necessity. Therefore, the identification of geotechnical design building features based on local and environmental conditions plays a fundamental role in improving the construction quality. Thus, given the increase of population in Tehran, the concentration in certain areas and the need to better identify soil characteristic for safer construction in these areas, a zoning study is performed in this study. The results showed that soils in regions 4 and 22 belong to B Tehran formation and are coarse. Because the soil is coarse-grained in these areas, earthquake liquefaction is not expected. Given the shear wave velocity in the 4 and 22 areas, the soil mass is characterized as dense or too dense.